2021
DOI: 10.1016/j.ajogmf.2021.100464
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination in pregnancy: early experience from a single institution

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 3 publications
9
68
3
1
Order By: Relevance
“…As one of the most frequent complications of early pregnancy is the spontaneous abortion, our study observed that the number of spontaneous abortions during the first trimester in COVID-19-vaccinated pregnant women was not significantly different from the normal incidence in the first trimester in unvaccinated pregnant women, as found in the control group, where pregnancy loss in the first trimester can occur in up to 20% of pregnancies [ 26 ]. In accordance with previously reported data [ 27 ], we noticed no concerning patterns for spontaneous abortions in the first trimester. However, other independent variables such as smoking, abnormal reproductive system anatomy, history of miscarriage, age and existing comorbidities were identified as significant risk factors in this study.…”
Section: Discussionsupporting
confidence: 92%
“…As one of the most frequent complications of early pregnancy is the spontaneous abortion, our study observed that the number of spontaneous abortions during the first trimester in COVID-19-vaccinated pregnant women was not significantly different from the normal incidence in the first trimester in unvaccinated pregnant women, as found in the control group, where pregnancy loss in the first trimester can occur in up to 20% of pregnancies [ 26 ]. In accordance with previously reported data [ 27 ], we noticed no concerning patterns for spontaneous abortions in the first trimester. However, other independent variables such as smoking, abnormal reproductive system anatomy, history of miscarriage, age and existing comorbidities were identified as significant risk factors in this study.…”
Section: Discussionsupporting
confidence: 92%
“…This is a surprising finding. A possible explanation may be found in persistent false messaging on social media that COVID-19 vaccines may cause infertility in females or birth defects [47,48]. Another surprising finding is that the study did not find a statistically significant difference in vaccine booster hesitancy among different racial or ethnic groups, which is contrary to our previous study (unpublished) and other studies [46,49], which showed a significant level of COVID-19 vaccine hesitancy among African Americans and Hispanics.…”
Section: Correlates Of Booster Hesitancycontrasting
confidence: 91%
“…Since the launch of the vaccinal campaign against SARS-CoV-2, the issue of pregnant women has been raised by the scientific community and the most important Obstetrics and Gynecology societies released recommendations in favor of it, but on the basis of a free choice of the pregnant woman, given the lack of data. However, reports showed quite soon that the vaccines were able to induce a response in pregnant women [43] , [44] , and that neither obvious safety issues were noticed in pregnant women and their fetuses or newborns [45] , nor a true change in pregnancy complications’ rates [63] . Moreover, the vaccine during pregnancy has been shown to reduce the risk of SARS-CoV-2 infection [64] .…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%